BUILDING A SHARIA-BASED ECONOMY: IMAM AL-GHAZALI'S THOUGHTS ON JUSTICE AND BALANCE IN THE MODERN ECONOMY - Samsul Muarif; Muhammad Yazid (JURNAL PROFIT, 2025)
This study explores the relevance of Imam al-Ghazali’s concepts of justice and balance in shaping a modern sharia-based economic system that is ethical, sustainable, and welfare-oriented. The research is grounded in a qualitative descriptive approach by analyzing al-Ghazali’s primary works alongside contemporary literature on Islamic economics. The findings show that al-Ghazali places justice as the essential foundation of economic life, emphasizing fairness in transactions, honesty, protection of rights, and the elimination of exploitation. His concept of balance highlights the importance of moderation, the avoidance of economic extremities, and the preservation of social stability. These principles strongly correspond with modern concerns regarding moral crises, inequality, market instability, and the need for ethical governance. The study concludes that al-Ghazali’s ethical framework provides substantial guidance for constructing economic policies that integrate spiritual values with economic rationality. His holistic perspective on human welfare, rooted in maslahah, demonstrates that economic development must incorporate both material and moral dimensions to achieve sustainable prosperity. The research contributes to the discourse on Islamic economics by offering a contemporary reinterpretation of classical thought and reinforcing its significance for addressing economic challenges in the modern era.